BASIS DAN DIMENSI ATAS PADA GRAF PEMBAGI NOL DARI RING KOMUTATIF - Inne Syafrian Putri; Bintang Puja Rahayu (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
Let be the set of nonzero divisors of the commutative ring . The zero divisor graph of is with the set of vertices , where two distinct vertices and are neighbors if and only if . The value of the upper dimension and the minimum solution set (base) of the zero divisor graph is finite. The steps to find the upper dimensions and base are from the specified ring, determine the zero divisor graph of the ring, and look for a different representation of . The set is called the solution set if all the vertices of have different representations of . In this study, some theorem about upper dimensions and base of the zero divisor graph of the commutative ring are discussed.